2021
DOI: 10.1055/s-0041-1731823
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Assist Device Driveline Infections: A Systematic Review

Abstract: Infection is the most common complication in patients undergoing ventricular assist device (VAD) implantation. Driveline exit site (DLES) infection is the most frequent VAD infection and is a significant cause of adverse events in VAD patients, contributing to morbidity, even mortality, and repetitive hospital readmissions. There are many risk factors for driveline infection (DLI) including younger age, smaller constitution of patients, obesity, exposed velour at the DLES, longer duration of device support, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 138 publications
2
9
1
Order By: Relevance
“…Some examples of patient characteristics that increase the risk of driveline infections are obesity, younger age, worse constitution, and longer time on device support [ 69 ]. Co-morbidities like diabetes, chronic kidney disease, and depression have also been associated with higher risk of driveline infection [ 69 ].…”
Section: Patient Management and Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Some examples of patient characteristics that increase the risk of driveline infections are obesity, younger age, worse constitution, and longer time on device support [ 69 ]. Co-morbidities like diabetes, chronic kidney disease, and depression have also been associated with higher risk of driveline infection [ 69 ].…”
Section: Patient Management and Optimizationmentioning
confidence: 99%
“…Some examples of patient characteristics that increase the risk of driveline infections are obesity, younger age, worse constitution, and longer time on device support [ 69 ]. Co-morbidities like diabetes, chronic kidney disease, and depression have also been associated with higher risk of driveline infection [ 69 ]. A single-center analysis showed that driveline infections are more common among HM3 patients, possibly due to the bigger size of the driveline in this device [ 70 ].…”
Section: Patient Management and Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, donor organ availability is strongly limited, and there is a growing number of destination therapy patients who will require alternative treatment in case of device infection [4]. This is particularly important, as otherwise established strategies such as antibiotic treatment or negative pressure wound therapy alone have not been able to provide an effective solution for device-related infections [5]. Lately, the rediscovery of bacteriophage therapy for the treatment of complex surgical infections has enabled a stimulating and novel, yet poorly investigated, option for VAD patients with device-related infections [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this, ventricular assist devices (VADs) can serve as a bridge to transplantation (BTT) or as destination therapy in this patient population 2–5. Yet, VAD support is not without its complications, with driveline infections (DLIs) being among the most commonly reported adverse event 6–11…”
Section: Introductionmentioning
confidence: 99%